Industrial engineering applications in emerging countries - Sabuncuoğlu, İhsan; Kara, Bahar Y; Bidanda, Bopaya (Engineering - Industrial & Manufacturing, 2015)
The second volume of a three-volume series on global logistics management, this book focuses on recent developments and implementations of operations research techniques on selected logistic problems in emerging countries. The book covers topics ranging from quality management in pharmaceutical supply chains to risk analysis of maritime ports and identifies quality management practices that impact supply chain performance using empirical data from pharmaceutical manufacturing sector in Pakistan. It provides case studies and discusses the application of IE tools